Assessing Gaming Simulation Validity for Training Traffic Controllers. (April 2017) - van Lankveld, G.; Sehic, E.; Lo, J. C.; Meijer, S. A.
Background. The Dutchrailway company ProRail is performing large-scale capacity upgrades to their infrastructure network. As part of these upgrades, ProRail usesgaming simulations to help preparetrain traffic controllers for new infrastructure situations. Researching thevalidity of these gaming simulations is essential, since the conclusions drawn from gaming simulation use may result in decisions with large financial and social impact for ProRail and Dutch train passengers. Aim. In this article, we aim to investigate the validity of the gaming simulations fortraining traffic controllers for new situations in rail infrastructure. We also aim to contribute to the discussion on the minimum level offidelity required to develop and conduct gaming simulations in a valid way. Method. We investigate the validity by using training sessions in conjunction withquestionnaires . We based the approach and questionnaires on the earlier work of Raser. Results. Our results show that the validity of the gaming simulation ranges from medium to good. They also show that while the fidelity of the gaming simulation is not like the real-world operating conditions, this does not reduce validity to low levels. Conclusions. We conclude that the gaming simulation used in this study was of medium to good validity. We also conclude that maximum fidelity is not required in order to run a valid gaming simulation session.